2017
DOI: 10.18203/2349-2902.isj20175099
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effect of intrathecal dexmedetomidine and clonidine as an adjuvant to hyperbaric bupivacaine in patients undergoing surgery for fracture femur and tibia

Abstract: Background: Spinal anaesthesia with bupivacaine is administered routinely for lower abdominal and lower limb surgeries. The ensuing nerve block is sufficient to ensure patient’s wellbeing, while motor block facilitates the surgeon’s work. Post-operative pain relief can be achieved by various methods namely systemic opioid and non-opioid peripheral nerve blocks and local wound infiltration, each with their own merits and demerits. the present study was undertaken to compare the effect of intrathecal dexmedetomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 19 publications
3
4
0
Order By: Relevance
“…4 We found a decrease in onset time of motor block after adding dexmedetomidine as compared to clonidine as measured by Bromage scale, the dfference being significant. Our findings are in accordance with Chandra et al 1 and Singh et al 10 and in contrast to Kanazi et al 4 The mean duration of receding time of sensory and motor block showed an increased duration of sensory block in dexmedetomidine group as compared to clonidine group. The difference between the groups was significant (P<0.05).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…4 We found a decrease in onset time of motor block after adding dexmedetomidine as compared to clonidine as measured by Bromage scale, the dfference being significant. Our findings are in accordance with Chandra et al 1 and Singh et al 10 and in contrast to Kanazi et al 4 The mean duration of receding time of sensory and motor block showed an increased duration of sensory block in dexmedetomidine group as compared to clonidine group. The difference between the groups was significant (P<0.05).…”
Section: Discussionsupporting
confidence: 92%
“…4 In the present study, it was found that, adding dexmedetomidine to bupivacaine decreased the time of onset of sensory block up to T10 level. These findings were similar to Chandra et al and Singh et al 1,10 However our findings were different from Kanazi et al who found that the onset of sensory block upto T10 level was faster for clonidine group (7.6 ± 4.4 mins) as compared to dexmedetomidine group (8.6±3.7 mins), but the difference found was not significant. 4 We found a decrease in onset time of motor block after adding dexmedetomidine as compared to clonidine as measured by Bromage scale, the dfference being significant.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations